2019
DOI: 10.1088/1748-0221/14/10/p10009
|View full text |Cite
|
Sign up to set email alerts
|

Large-area Si(Li) detectors for X-ray spectrometry and particle tracking in the GAPS experiment

Abstract: Large-area lithium-drifted silicon (Si(Li)) detectors, operable 150 • C above liquid nitrogen temperature, have been developed for the General Antiparticle Spectrometer (GAPS) balloon mission and will form the first such system to operate in space. These 10 cm-diameter, 2.5 mm-thick multi-strip detectors have been verified in the lab to provide < 4 keV FWHM energy resolution for X-rays as well as tracking capability for charged particles, while operating in conditions (∼-40C and ∼1 Pa) achievable on a long-dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Thanks to the sufficiently low leakage currents, it has been confirmed that energy resolution 4 keV (FWHM) for 20−100 keV X-rays are achieved [46]. Details of the energy resolution measurements are described in a separate publication [15]. Figure 9 illustrates the setup for the I−V curve measurement.…”
Section: Performance Of the Mass-produced Detectorsmentioning
confidence: 88%
See 3 more Smart Citations
“…Thanks to the sufficiently low leakage currents, it has been confirmed that energy resolution 4 keV (FWHM) for 20−100 keV X-rays are achieved [46]. Details of the energy resolution measurements are described in a separate publication [15]. Figure 9 illustrates the setup for the I−V curve measurement.…”
Section: Performance Of the Mass-produced Detectorsmentioning
confidence: 88%
“…The upper panel of Fig. 10 displays I−V curves of 8 strips of a sample detector at −35 • C. The leakage current of each strip is stable and is ∼1.5 nA at our operating voltage (200−300 V), significantly lower than the requirement, ∼5 nA [15]. The capacitance as a function of the bias voltage in the lower panel of Fig.…”
Section: Performance Of the Mass-produced Detectorsmentioning
confidence: 94%
See 2 more Smart Citations
“…GAPS presents unique challenges for Si(Li) detector construction, operation and performance. The large detector area, low noise, and high temperature requirements have been met by developing a new fabrication technique, as described in detail in [13] and [14]. These detectors have been designed with a top-hat structure containing eight equal-area strips surrounded by a guard ring ( fig.…”
Section: Si(li) Detectorsmentioning
confidence: 99%